‘Now the neighbors lose their fear’: restoring the social network around former sites of terror in Argentina - Schindel, Estela (International journal of transitional justice, 2012)
State terror in Argentina in the late 1970s was aimed at dismantling social relationships of mutual commitment and solidarity and imposing in their stead practices of fear, isolation and mistrust. A permeating network of clandestine detention centers and illegal burial sites played a key role in spreading localized state terror to the whole of society. After describing the broader context of the dictatorship’s urban space restructuring policy, this article explores various practices currently taking place in former clandestine detention centers ‘recovered’ by civilians. The author suggests that the opening of these centers allows the emergence of narratives and everyday practices that can counteract the ones that prevailed under the dictatorship, fostering the opposite effect - active citizenship, counternarratives of terror and restored social networks. This approach highlights potential uses of memorial sites that have not received enough attention to date. Moreover, it can act as a bridge between the paradigm of transitional justice and the developments and aims of spatial justice.